The model village, new-style - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Models are a superb way to explain a phenomenon and to raise questions, through which an extension worker can ascertain the depth of knowledge in a community. Made by the people themselves and using materials available in the village (tools,...